2020
DOI: 10.3390/atmos11010052
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Investigation of the Berg Feature on Uranus as a Vortex-Driven System

Abstract: The Berg cloud feature in the atmosphere of Uranus was first identified as a persistent grouping of clouds located just off the bright South Polar Collar at a latitude of around −34 degrees. Ongoing observations of this feature through the 1990s and 2000s suggested that the feature was oscillating in location by a few degrees in latitude for several years, and then unexpectedly began to drift towards the equator, which continued over the final 4 years until the cloud dissipated. One possible explanation for su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In addition to β , any PV gradient in the background of a cyclone (e.g., by a jet or a nearby cyclone) can similarly influence its motion (Chan & Law, 1995; Shin et al., 2006; Rivière et al., 2012). For example, the PV gradient due to the zonal mean wind shear and β was shown, using full 3D models, to drive the meridional motion of large vortices on Uranus (LeBeau et al., 2020) and Neptune (LeBeau & Dowling, 1998). It was recently found that latitude ∼84°, where the CPCs are observed at both poles of Jupiter, is the latitude where the beta‐drift is balanced by an equivalent vorticity‐gradient force, in which the source of the PV gradient field is the PC instead of the planetary β (Gavriel & Kaspi, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to β , any PV gradient in the background of a cyclone (e.g., by a jet or a nearby cyclone) can similarly influence its motion (Chan & Law, 1995; Shin et al., 2006; Rivière et al., 2012). For example, the PV gradient due to the zonal mean wind shear and β was shown, using full 3D models, to drive the meridional motion of large vortices on Uranus (LeBeau et al., 2020) and Neptune (LeBeau & Dowling, 1998). It was recently found that latitude ∼84°, where the CPCs are observed at both poles of Jupiter, is the latitude where the beta‐drift is balanced by an equivalent vorticity‐gradient force, in which the source of the PV gradient field is the PC instead of the planetary β (Gavriel & Kaspi, 2021).…”
Section: Introductionmentioning
confidence: 99%
“… 2019a ; LeBeau et al. 2020 ), but no vortex rotation was directly resolved, and dramatic brightening events were interpreted as potential convective outbursts related to the feature (de Pater et al. 2011 ).…”
Section: Spatial Variation In the Uranus Atmospherementioning
confidence: 99%